Industrialization of Nature in the Time of Complexity Unawareness: The Case of Chitgar Lake, Iran. (March 2022) - Akhshik, Arash; Rezapouraghdam, Hamed; Ramkissoon, Haywantee
To find answers to the challenges linked with ecological well-being, policymakers and authorities now prefer the ecosystem-based approach, as the solutions inspired by nature may deflect from ecological collapse. Nature-based solutions (NBS) are rhapsodized both in practice and academia as a means to achieve sustainable development. However, NBS, which inherently is supposed to bring forth positive outcomes, may also lead to unsustainable turmoil. On the other hand, the majority of the studies about NBS are from Western countries and studies focusing on the paradoxical functionality of NBS are scant, especially in the Middle East. In an attempt to bridge this gap, the current study uses one of the largest blue artificial infrastructures in the Middle East as a case. Following the phenomenological interpretive approach, the authors argue that NBS may fabricate unintended problems when the complexity of the supra systems are overlooked. Theoretical and practical contributions are discussed.